HUBUNGAN RANGSANGAN PUTING SUSU DENGAN PEMBUKAAN SERVIK KALA I FASE AKTIF PADA IBU PRIMIGRAVIDA DI BPS HJ. ISYANA YUDHA CANGGU KECAMATAN JETIS KABUPATEN MOJOKERTO - Lestari, Indah; Kusniah, Etik (JURNAL KEPERAWATAN BINA SEHAT, 2011)
Childbirth is the process where the baby, placenta and amniotic membranes out of the mothers uterus. Long confinement is still a problem in Indonesia, therefore these cases theres also a long confinement, and this situation forces us to try to reduce the number of maternal and child deaths and reduce the sense of maternal morbidity during labor. Which is ideal of course how to prevent long parturition. The purpose of this study was to determine the relationship nipple stimulation at the opening of the first stage of the active phase. The design of this study is the correlation of Analytical. Population was all mothers who are inpartu at BPS Hj. Isyana Yudha Amd. Keb in the village of Canggu, Jetis Subdistrict, Mojokerto regency. The sample consisted of 10 respondents by means of sample selection Consecutive Sampling. Independent variables: stimulation of the nipple and the dependent variable: the speed of the opening of the first stage of the active phase. The instruments used are the SOPs and patograf. The results presented in the form of tables and data processing with the Spearman Rho test to determine the relationship between variables. Results of analysis of data shows the value ρ = 0.006 with α = 0.05 where H0is rejected it means there is a connection between nipple stimulation with the opening speed. This suggests that there is a very strong relationship between nipple stimulation at the opening of the first stage of the active phase. From the results of research can be concluded that stimulation of the nipples causes the off-load synchronous high frequency of oxytocin neurons after a latent phase. Increased secretion of oxytocin during labor, after dilatsi cervical fetal descent through the birth canal implus spark emitted in the efferent nerves to the supraoptic and paraventrikel menyebebkan oxytocin in sufficient quantities to speed up labor.Keywords: nipple stimulation, the cervical opening.